Soil mechanics in engineering practice - Terzaghi, Karl; Peck, Ralph. B (Cairo modern egyptian bureau, 1986)
This book is one of the best-known and most respected books in geotechnical engineering. In its third edition, it presents both theoretical and practical knowledge of soil mechanics in engineering. It features expanded coverage of vibration problems, mechanics of drainage, passive earth pressure, and consolidation
12 20
Keywords: Mechanics; Soil mechanics